Processing technology of zirconia ceramic mobile phone rear cover
By adding specific materials to the processing process of the back cover of the zirconia ceramic mobile phone and adopting multi-step molding and processing processes, the processing problems caused by the high brittleness of zirconia ceramics are solved, and the toughness and processing performance of the product are significantly improved, and the breakage and scrap rate are reduced.
Patent Information
- Application Number
- CN202411882660.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Due to its high hardness and high density characteristics, the brittleness of the zirconia ceramic mobile phone back cover is increased, which makes it easy to cause internal stress concentration due to external forces during processing, resulting in damage or scrapping of the product.
A processing process is adopted, including pretreating zirconia powder to improve its brittleness, by adding materials such as polylactic acid, hydroxysilane coupling agent, zinc oxide and nanocellulose crystals, to enhance the toughness and strength of the ceramic, and reduce internal stress and defects through dry and static pressure forming, sintering, precision processing and surface treatment.
It significantly improves the toughness and processing performance of the back cover of the zirconia ceramic mobile phone, reduces the breakage rate and scrap rate during the processing, improves the yield rate, and ensures the high hardness and high density characteristics of the ceramic body.
Smart Images

Figure BDA0005198571150000101 
Figure BDA0005198571150000111
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of ceramic mobile phone back cover processing, and more specifically, to a processing technology for a zirconia ceramic mobile phone back cover. Background Art
[0002] With the continuous evolution of mobile communication technology and the increasing personalized needs of consumers, mobile phones have become an indispensable communication and entertainment tool in daily life, and their structural materials and design styles have become one of the important considerations for users to choose. Among them, zirconia ceramic mobile phone back covers are deeply loved by people because of their high durability, high aesthetics, good heat dissipation and environmental protection. Specifically, zirconia ceramics have high hardness, which can significantly improve the scratch and impact resistance of the mobile phone back cover; at the same time, its high wear resistance ensures that the mobile phone back cover can still maintain excellent surface quality during long-term use; furthermore, the high corrosion resistance gives the mobile phone back cover stable physical and chemical properties in complex and changeable use environments, further extending the service life of the product.
[0003] However, although the high hardness and high density of zirconia ceramics have brought about a significant improvement in durability, it has also led to an increase in the brittleness of zirconia ceramics, making it very easy for external forces (such as cutting, grinding, polishing, etc.) to cause internal stress concentration during the processing of zirconia ceramic mobile phone back covers, ultimately leading to product damage or scrapping and low production efficiency. Summary of the invention
[0004] In order to solve the problem that zirconia ceramics are brittle and cause products to be easily damaged or scrapped, the present application provides a processing technology for zirconia ceramic mobile phone back cover In the first aspect, the present application provides a processing technology for a zirconia ceramic mobile phone back cover, which adopts the following technical solution: A processing technology for a zirconium oxide ceramic mobile phone back cover comprises the following preparation steps: S1, dissolving polylactic acid and hydroxysilane coupling agent in an organic solvent, adding zirconium oxide powder, heating to 40-50°C, ultrasonicating, filtering, and drying to obtain pretreated zirconium oxide powder; S2, kneading the pretreated zirconium oxide powder, zinc oxide, nanocellulose crystals, the first dispersant, the binder and the plasticizer to obtain a mixture; S3, dry pressing the mixture with a dry press, cooling it, and placing it in a static press for isostatic pressing to obtain an embryo; S4, debinding and sintering the embryo body to obtain a ceramic body; S5. Use CNC machine tools to perform precision machining on the ceramic body to achieve the required size and shape accuracy; S6, using a grinder and a polisher in sequence to finely process the surface of the ceramic body; S7, performing beautification treatment and anti-fingerprint treatment on the surface treated ceramic body to obtain a ceramic mobile phone case back cover.
[0005] By adopting the above technical solution, the toughness and processing performance of the zirconia ceramic mobile phone back cover can be effectively improved, the breakage rate and scrap rate during the processing can be reduced, and the yield rate of the zirconia ceramic mobile phone back cover can be improved.
[0006] In step S1, polylactic acid, as a biodegradable plastic, has good toughness and ductility. By dissolving polylactic acid and hydroxy silane coupling agent in an organic solvent, polylactic acid is effectively coated on the surface of zirconia powder under the action of hydroxy silane coupling agent and ultrasonic treatment at elevated temperature, which helps to improve the brittleness of zirconia ceramics and improve the toughness of zirconia ceramics. That is, pretreatment provides a basis for subsequent processing, helps to reduce internal stress concentration, and improves the anti-breakage ability of zirconia ceramics.
[0007] Nanocellulose crystals can enhance the overall strength and toughness of the ceramic body due to their high strength and high modulus properties; zinc oxide reacts with other components to form a tougher compound by forming a grain boundary phase, so the addition of zinc oxide and nanocellulose crystal additives in step S2 can further enhance the toughness and strength of the oxide ceramic. The addition of the first dispersant, binder and plasticizer helps to improve the processing properties of the material, making it easier to shape and process.
[0008] In step S3, after dry pressing by a dry press, isostatic pressing is performed to ensure that the ceramic body has a uniform density and a compact structure, thereby reducing internal defects and stress concentration.
[0009] The sintering process in step S4 densifies the ceramic body, forms a stable crystal structure, and improves the structural stability of the zirconia ceramic. At the same time, precision machining using CNC machine tools can ensure that the ceramic body reaches the required size and shape accuracy, while reducing the risk of breakage during machining. Grinding and polishing further improve the surface finish and quality of the ceramic body.
[0010] The beautification treatment in step S5 not only improves the appearance quality of the product, but also may further enhance the wear resistance and anti-fingerprint performance of the ceramic body through a specific coating or treatment process.
[0011] Preferably, the weight percentages of the raw materials used in step S2 are as follows: Pre-treated zirconium oxide powder 50-60% Zinc oxide 8-15% Plasticizer 1-2% First dispersant 2-5% Binder 6-9% The rest is nanocellulose crystals.
[0012] By adopting the above technical solution, the weight of the raw materials used in step S2 is optimized, the toughness of the zirconia ceramic is further improved, and at the same time the high hardness and high density characteristics of the ceramic body are ensured, the breakage rate and scrap rate during the processing are reduced, thereby improving production efficiency and economic benefits.
[0013] Preferably, in step S1, the weight ratio of polylactic acid, hydroxysilane coupling agent, organic solvent and zirconium oxide powder is 1:0.5:5:(2-3).
[0014] By adopting the above technical scheme, the weight ratio of polylactic acid, hydroxysilane coupling agent, organic solvent and zirconium oxide powder is optimized, the bonding rate of zirconium oxide powder and polylactic acid is increased, the influence of the brittleness of zirconium oxide powder on zirconium oxide ceramics is further reduced, the breakage rate of ceramic bodies in subsequent processing is reduced, and the yield and product quality are improved.
[0015] Preferably, the banburying temperature in step S2 is 170-180° C. and the time is 1-2 h.
[0016] By adopting the above technical scheme, the mixing temperature and time are optimized, and the fluidity of the pretreated zirconium oxide powder, zinc oxide, nanocellulose crystals, the first dispersant, the binder and the plasticizer is enhanced, which is beneficial to their full mixing and uniform distribution to form a stable mixture, so that a tighter and more uniform structure can be formed in the subsequent molding and sintering process, thereby improving the strength and toughness of the ceramic body.
[0017] Preferably, the pressure during the isostatic pressing is 220-280 MPa, and the holding time is 4-6 min.
[0018] By adopting the above technical solution, the pressure in isostatic pressing is optimized so that the zirconia ceramic body is subjected to balanced pressure, which helps to eliminate the pores and defects inside the body and improve the density and uniformity of the material. At the same time, the holding time is controlled at 4-6 minutes, which can ensure that the body is fully compacted and solidified under high pressure without causing overheating or deformation of the material.
[0019] Preferably, in step S4, the embryo body is placed in an environment of 700-900° C. for debinding.
[0020] By adopting the above technical solution, the plasticizer in the embryo is effectively removed, avoiding the pyrolysis or volatilization of the plasticizer during the subsequent sintering process to produce bubbles, cracks and other defects, which affect the quality and performance of the ceramic body. The embryo after debinding is easier to achieve densification during the sintering process, which helps to obtain a higher quality ceramic body and improve the product yield and performance stability.
[0021] Preferably, the sintering process in step S4 is as follows: First sintering: sinter the debinded green body at 1500-1600℃ for 12-15h; Second sintering: sinter the green body after the first sintering at 1650-1750℃ for 10-12h; Third sintering: Sinter the green body after the second sintering at 1400-1500°C for 12-14h.
[0022] By adopting the above technical solution. A three-stage sintering is adopted to gradually optimize the microstructure of zirconia ceramics, improve mechanical properties and eliminate internal stress. The first sintering causes the zirconia particles to begin to partially sinter, forming preliminary grain boundaries and grain structures. The grain boundaries between the zirconia particles in the second sintering are clearer, the grains begin to grow, and a denser microstructure is formed. The density of the green body reaches a high level, and the porosity is reduced. At this time, the densified microstructure and crystal phase transformation work together to improve the strength of the ceramic, thereby improving its mechanical properties such as flexural strength and compressive strength. The third sintering helps to further adjust and optimize the microstructure of the ceramic, reduce excessively large grains, and make the grain distribution more uniform, thereby improving the overall performance of the ceramic. At the same time, long-term low-temperature sintering helps to eliminate the internal stress caused by the first two high-temperature sinterings, and helps to reduce the risk of cracking of the ceramic during subsequent processing or use.
[0023] Preferably, the ceramic body is ground in step S6, and the grinding process is as follows: 1) mixing agglomerated diamond micropowder, a second dispersant, a first suspending agent, a first lubricant and a first solvent to obtain a grinding liquid; 2) Use grinding liquid and a honeycomb resin pad grinding wheel to grind the ceramic body. The pressure of the honeycomb resin pad grinding wheel is 90-100g / cm2, the rotation speed is 60-90r / min, and the flow rate is 500-600ml / min.
[0024] Preferably, the weight ratio of the agglomerated diamond powder, the second dispersant, the first suspending agent, the first lubricant and the first solvent is 1:0.5:0.3:0.5:(4-6).
[0025] Preferably, in step S6, the ceramic body is polished, and the polishing process is as follows: A: mixing silicon dioxide, sodium oxide, a third dispersant, a second suspending agent, a second lubricant and a second solvent to obtain a polishing liquid; B: Use polishing liquid and non-woven polishing wheel to polish the ceramic body. The pressure of the non-woven polishing wheel is 150-170g / cm2, the speed is 120-150r / min, and the flow rate is 600-800ml / min.
[0026] Preferably, the weight ratio of silicon dioxide, sodium oxide, the third dispersant, the second suspending agent, the second lubricant and the second solvent is 2:0.5:0.5:0.3:0.5:(4-6).
[0027] By adopting the above technical solution and optimizing the grinding liquid composition and grinding parameters, the polishing liquid composition and polishing parameters, it is possible to efficiently remove excess material on the surface of the zirconia ceramic mobile phone back cover, while ensuring that the zirconia ceramic mobile phone back cover does not crack or break during the grinding process.
[0028] The particle size of the agglomerated diamond powder is 50-100 nm, and the particle size of the silicon dioxide is 10-30 nm.
[0029] By adopting the above technical solution, the particle size of agglomerated diamond micropowder and silicon dioxide is optimized, the efficiency of grinding and polishing is improved, and at the same time, damage to the back cover of the zirconia ceramic mobile phone caused by large particles is avoided.
[0030] In summary, this application has the following beneficial effects: 1. By adding materials such as polylactic acid, hydroxy silane coupling agent, zinc oxide and nanocellulose crystals, the toughness of zirconia ceramics is significantly improved and the breakage rate during processing is reduced. At the same time, the improvement of pretreatment and molding process makes the ceramic embryo easier to process, reducing the formation of internal stress and defects. The introduction of precision machining and surface treatment technology ensures the high precision and high quality of the back cover of the ceramic mobile phone case, while meeting the needs of beauty and practicality. DETAILED DESCRIPTION Example
[0031] Polylactic acid was purchased from Hubei Xinyuhong Biopharmaceutical Technology Co., Ltd. with the model number N / A.
[0032] The non-woven fabric polishing wheel is obtained by pasting non-woven fabric on a polishing wheel. The non-woven fabric is purchased from Tianjin Junteng Technology Co., Ltd. and the model is TexMetP.
[0033] Agglomerated diamond powder was purchased from Henan Hengwei Superhard Materials Co., Ltd. with a model of 0.1-600.
[0034] The honeycomb resin pad grinding wheel is obtained by sticking a honeycomb resin pad on a grinding wheel. The honeycomb resin pad was purchased from Wuxi Jizhi Electronic Technology Co., Ltd., and the model is jzdz-1028.
[0035] The montmorillonite suspension was purchased from Lingshou County Huixin Mining Processing Plant with a specification of 325 mesh, an apparent viscosity of 600 mPa.s, and a hardness of 2.0-2.5.
[0036] Example 1 A processing technology for a zirconium oxide ceramic mobile phone back cover comprises the following preparation steps: S1, dissolving 250 g of polylactic acid and 125 g of hydroxy silane coupling agent (3-hydroxypropyltrimethoxysilane) in 1250 g of organic solvent (chloroform), adding 500 g of zirconium oxide powder, heating to 40° C., ultrasonicating, filtering, and drying to obtain pretreated zirconium oxide powder; S2, kneading 500 g of pretreated zirconium oxide powder, 150 g of zinc oxide, 200 g of nanocellulose crystals, 50 g of a first dispersant (hydroxypropyl methylcellulose), 90 g of a binder (polyvinyl alcohol, molecular weight 10,000) and 10 g of a plasticizer (dibutyl phthalate) at a kneading temperature of 170° C. for 1 h to obtain a mixture; S3, dry pressing the mixture with a dry press, cooling it, and then placing it in a static press for isostatic pressing, wherein the pressure during isostatic pressing is 220 MPa and the holding time is 4 min, to obtain an embryo body; S4, placing the embryo body in a 700°C environment for debinding and sintering. The sintering process in step S4 is as follows: First sintering: sinter the debinded green body at 1500℃ for 12h; Second sintering: sinter the green body after the first sintering at 1650℃ for 10h; Third sintering: sinter the green body after the second sintering at 1400°C for 12h to obtain a ceramic body; S5. Use CNC machine tools to perform precision machining on the ceramic body to achieve the required size and shape accuracy; S6, using a grinder and a polisher in sequence to finely process the surface of the ceramic body; The grinding process is as follows: 1) agglomerated diamond micropowder, a second dispersant (hydroxypropyl methylcellulose), a first suspending agent (montmorillonite suspending agent), a first lubricant (fatty alcohol polyoxyethylene ether) and a first solvent (water) are mixed to obtain a grinding liquid, wherein the weight ratio of agglomerated diamond micropowder, the second dispersant, the first suspending agent, the first lubricant and the first solvent is 1:0.5:0.3:0.5:4, and the particle size of the agglomerated diamond micropowder is 50-100 nm; 2) Use grinding liquid and a honeycomb resin pad grinding wheel to grind the ceramic body. The pressure of the honeycomb resin pad grinding wheel is 90g / cm2, the rotation speed is 60r / min, and the flow rate is 500ml / min.
[0037] The polishing process is as follows: A: Silicon dioxide, sodium oxide, a third dispersant (hydroxypropyl methylcellulose), a second suspending agent (stone-removing suspending agent), a second lubricant (nonylphenol polyoxyethylene ether) and a second solvent (water) are mixed to obtain a polishing liquid, wherein the weight ratio of silicon dioxide, sodium oxide, the third dispersant, the second suspending agent, the second lubricant and the second solvent is 2:0.5:0.5:0.3:0.5:4, and the particle size of silicon dioxide is 10-30 nm; B: Use polishing liquid and non-woven polishing wheel to polish the ceramic body. The pressure of the non-woven polishing wheel is 150g / cm2, the speed is 120r / min, and the flow rate is 600ml / min.
[0038] S7, performing beautification treatment and anti-fingerprint treatment on the surface treated ceramic body to obtain a ceramic mobile phone case back cover.
[0039] Example 2 A processing technology for a zirconium oxide ceramic mobile phone back cover comprises the following preparation steps: S1, dissolving 200 g of polylactic acid and 100 g of hydroxy silane coupling agent (3-hydroxypropyltrimethoxysilane) in 1000 g of organic solvent (tetrahydrofuran), adding 500 g of zirconium oxide powder, heating to 45° C., ultrasonicating, filtering, and drying to obtain pretreated zirconium oxide powder; S2, 550g of pretreated zirconium oxide powder, 120g of zinc oxide, 205g of nanocellulose crystals, 35g of a first dispersant (sodium carboxymethyl cellulose), 60g of a binder (polyethylene glycol, molecular weight 20000) and 15g of a plasticizer (dibutyl phthalate) were kneaded at a temperature of 175°C for 1.5h to obtain a mixture; S3, dry-pressing the mixture with a dry press, cooling it, and then placing it in a static press for isostatic pressing, wherein the pressure during isostatic pressing is 260 MPa and the holding time is 5 min to obtain an embryo body; S4, placing the embryo body in an environment of 800°C for debinding and sintering. The sintering process in step S4 is as follows: First sintering: sinter the debinded green body at 1550℃ for 14h; Second sintering: sinter the green body after the first sintering at 1700℃ for 11h; The third sintering: the green body after the second sintering is sintered at 1450°C for 13h to obtain a ceramic body; S5. Use CNC machine tools to perform precision machining on the ceramic body to achieve the required size and shape accuracy; S6, using a grinder and a polisher in sequence to finely process the surface of the ceramic body; The grinding process is as follows: 1) agglomerated diamond micropowder, a second dispersant (sodium carboxymethyl cellulose), a first suspending agent (montmorillonite suspending agent), a first lubricant (nonylphenol polyoxyethylene ether) and a first solvent (water) are mixed to obtain a grinding liquid, wherein the weight ratio of agglomerated diamond micropowder, the second dispersant, the first suspending agent, the first lubricant and the first solvent is 1:0.5:0.3:0.5:5, and the particle size of the agglomerated diamond micropowder is 50-100 nm; 2) Use grinding liquid and a honeycomb resin pad grinding wheel to grind the ceramic body. The pressure of the honeycomb resin pad grinding wheel is 95g / cm2, the rotation speed is 70r / min, and the flow rate is 550ml / min.
[0040] The polishing process is as follows: A: Mix silica, sodium oxide, a third dispersant (sodium carboxymethyl cellulose), a second suspending agent (montmorillonite suspending agent), a second lubricant (nonylphenol polyoxyethylene ether) and a second solvent (water) to obtain a polishing liquid, wherein the weight ratio of silica, sodium oxide, the third dispersant, the second suspending agent, the second lubricant and the second solvent is 2:0.5:0.5:0.3:0.5:5, and the particle size of silica is 10-30 nm; B: Use polishing liquid and non-woven polishing wheel to polish the ceramic body. The pressure of the non-woven polishing wheel is 160g / cm2, the speed is 135r / min, and the flow rate is 700ml / min.
[0041] S7, performing beautification treatment and anti-fingerprint treatment on the surface treated ceramic body to obtain a ceramic mobile phone case back cover.
[0042] Example 3 A processing technology for a zirconium oxide ceramic mobile phone back cover comprises the following preparation steps: S1, dissolving 158 g of polylactic acid and 76 g of hydroxy silane coupling agent (3-hydroxypropyltrimethoxysilane) in 790 g of organic solvent (dimethylformamide), adding 500 g of zirconium oxide powder, heating to 50° C., ultrasonicating, filtering, and drying to obtain pretreated zirconium oxide powder; S2, kneading 500 g of pretreated zirconium oxide powder, 80 g of zinc oxide, 220 g of nanocellulose crystals, 50 g of a first dispersant (triethanolamine), 60 g of a binder (carboxymethyl cellulose) and 20 g of a plasticizer (dioctyl phthalate) at a kneading temperature of 180° C. for 2 h to obtain a mixture; S3, dry-pressing the mixture with a dry press, cooling it, and placing it in a static press for isostatic pressing, wherein the pressure during isostatic pressing is 280 MPa and the holding time is 6 min to obtain an embryo body; S4, placing the embryo body in a 900°C environment for debinding and sintering. The sintering process in step S4 is as follows: First sintering: sinter the debinded green body at 1600℃ for 15h; Second sintering: sinter the green body after the first sintering at 1750℃ for 12h; Third sintering: sinter the green body after the second sintering at 1500°C for 14h to obtain a ceramic body; S5. Use CNC machine tools to perform precision machining on the ceramic body to achieve the required size and shape accuracy; S6, using a grinder and a polisher in sequence to finely process the surface of the ceramic body; The grinding process is as follows: 1) agglomerated diamond powder, a second dispersant (triethanolamine), a first suspending agent (montmorillonite suspending agent), a first lubricant (linseed oil) and a first solvent (water) are mixed to obtain a grinding liquid, wherein the weight ratio of agglomerated diamond powder, the second dispersant, the first suspending agent, the first lubricant and the first solvent is 1:0.5:0.3:0.5:6, and the particle size of the agglomerated diamond powder is 50-100 nm; 2) Use grinding liquid and a honeycomb resin pad grinding wheel to grind the ceramic body. The pressure of the honeycomb resin pad grinding wheel is 100g / cm2, the rotation speed is 90r / min, and the flow rate is 600ml / min.
[0043] The polishing process is as follows: A: silica, sodium oxide, a third dispersant (triethanolamine), a second suspending agent (montmorillonite suspending agent), a second lubricant (linseed oil) and a second solvent (water) are mixed to obtain a polishing liquid, wherein the weight ratio of silica, sodium oxide, the third dispersant, the second suspending agent, the second lubricant and the second solvent is 2:0.5:0.5:0.3:0.5:6, and the particle size of silica is 10-30 nm; B: Use polishing liquid and non-woven polishing wheel to polish the ceramic body. The pressure of the non-woven polishing wheel is 170g / cm2, the speed is 150r / min, and the flow rate is 800ml / min.
[0044] S7, performing beautification treatment and anti-fingerprint treatment on the surface treated ceramic body to obtain a ceramic mobile phone case back cover.
[0045] Example 4 A processing technology for a zirconia ceramic mobile phone back cover, the difference between this embodiment and embodiment 1 is that the pressure in isostatic pressing is 200 MPa.
[0046] Example 5 A processing technology for a zirconia ceramic mobile phone back cover. The difference between this embodiment and embodiment 1 is that the pressure in isostatic pressing is 300 MPa.
[0047] Example 6 A processing technology for a zirconia ceramic mobile phone back cover, the difference between this embodiment and embodiment 1 is that the banburying temperature of step S2 is 160°C.
[0048] Example 7 A processing technology for a zirconia ceramic mobile phone back cover, the difference between this embodiment and embodiment 1 is that the particle size of the agglomerated diamond micropowder is 150-200nm.
[0049] Example 8 A processing technology for a zirconium oxide ceramic mobile phone back cover, the difference between this embodiment and embodiment 1 is that the particle size of silicon dioxide is 40-50nm.
[0050] Example 9 A processing technology for a zirconia ceramic mobile phone back cover. The difference between this embodiment and embodiment 1 is that the pressure of the honeycomb resin pad grinding wheel is 110g / cm 2 .
[0051] Example 10 A processing technology for a zirconia ceramic mobile phone back cover, the difference between this embodiment and embodiment 1 is that the honeycomb resin pad grinding wheel is replaced by an optical fiber grinding rubber pad.
[0052] The optical fiber polishing pad was purchased from Shenzhen Newfiber Technology Co., Ltd., model PR5X-480-80.
[0053] Embodiment 11 A processing technology for a zirconia ceramic mobile phone back cover. The difference between this embodiment and embodiment 1 is that the pressure of the non-woven polishing wheel is 180g / cm 2 .
[0054] Example 12 A processing technology for a zirconia ceramic mobile phone back cover. The difference between this embodiment and embodiment 1 is that the non-woven polishing wheel is replaced by a Fangda damping cloth polishing pad wafer grinding pad.
[0055] The Fangda damping cloth polishing pad and wafer grinding pad were purchased from Shenzhen Fangda Grinding Technology Co., Ltd., model 380.
[0056] Example 13 A processing technology for a zirconia ceramic mobile phone back cover. The difference between this embodiment and embodiment 1 is that the sintering process in step S4 is as follows: The debinded green body was sintered at 1650°C for 34 hours to obtain a ceramic body.
[0057] Embodiment 14 A processing technology for a zirconia ceramic mobile phone back cover. The difference between this embodiment and embodiment 1 is that the sintering process in step S4 is as follows: First sintering: sinter the debinded green body at 1650℃ for 22h; Second sintering: The green body after the second sintering is sintered at 1400° C. for 12 hours to obtain a ceramic body.
[0058] Comparative Example Comparative Example 1 A processing technology for a zirconia ceramic mobile phone back cover, the difference between this comparative example and Example 1 is that polylactic acid is not added in step S1.
[0059] Comparative Example 2 A processing technology for a zirconium oxide ceramic mobile phone back cover, the difference between this comparative example and Example 1 is that no hydroxy silane coupling agent is added in step S1.
[0060] Comparative Example 3 A processing technology for a zirconia ceramic mobile phone back cover, the difference between this comparative example and Example 1 is that step S1 is omitted.
[0061] Comparative Example 4 A processing technology for a zirconia ceramic mobile phone back cover. The difference between this comparative example and Example 1 is that glass powder is used instead of nanocellulose crystals in step S2.
[0062] The glass powder was purchased from Shuangshi Mineral Products Processing Plant in Lingshou County with specifications of 325 mesh and 600 mesh.
[0063] Comparative Example 5 A processing technology for a zirconium oxide ceramic mobile phone back cover. The difference between this comparative example and Example 1 is that aluminum oxide is used instead of zinc oxide in step S2.
[0064] Inspection method / test method: Inspection of good products: prepare zirconia ceramic mobile phone case back covers according to the methods of Examples 1-14 and Comparative Examples 1-5, and prepare 25 zirconia ceramic mobile phone case back covers in each Example or Comparative Example. Inspect the zirconia ceramic mobile phone case back covers to see if there are cracks, fine lines, etc. on the zirconia ceramic glass mobile phone case back covers, and count how many zirconia ceramic mobile phone case back covers have the above-mentioned conditions in each Example.
[0065] Strength test: Take out one intact zirconia ceramic mobile phone case back cover prepared from Examples 1-14 and Comparative Examples 1-5, respectively, and use a universal testing machine to test the three-point bending strength of the zirconia ceramic mobile phone case back cover.
[0066] Hardness test: Take out one intact zirconia ceramic mobile phone case back cover prepared from Examples 1-14 and Comparative Examples 1-5, respectively, and measure its hardness using a Vickers hardness tester (diamond indenter, force 10 kg, test time 15 s).
[0067] Drop test: Find a horizontal cement floor, take out one intact zirconia ceramic mobile phone case back cover prepared from Examples 1-14 and Comparative Examples 1-5, and drop it freely from a height of 6m above the cement floor to observe whether the zirconia ceramic mobile phone case back cover is cracked or broken. The experimental data are shown in Table 1: Table 1 Experimental data of Examples 1-14 and Comparative Examples 1-5 Comparing Example 1 with Comparative Examples 1-5, there are more defective products in Comparative Examples 1-5, while there is no defective product in Example 1; the strength and hardness of Comparative Examples 1-5 are not as good as those of Example 1; Comparative Examples 1-5 were cracked and broken in the drop test, indicating that by optimizing the process steps and types of raw materials in this application, the yield rate of the back cover of the zirconia ceramic mobile phone case can be improved, and the strength, hardness and drop resistance of the back cover of the zirconia ceramic mobile phone case can also be improved.
[0068] Comparing Example 1 with Example 4-5, defective products appeared in Example 4-5, and the strength and hardness of Example 4-5 were not as good as those of Example 1, indicating that optimizing the pressure in isostatic pressing can help improve the yield rate of the back cover of zirconia ceramic mobile phone cases, and can also improve the strength and hardness of the back cover of zirconia ceramic mobile phone cases.
[0069] Comparing Example 1 with Example 6, defective products are found in Example 6, and the strength and hardness of Example 6 are not as good as those of Example 1, indicating that optimizing the mixing temperature is beneficial to improving the yield rate of the back cover of the zirconia ceramic mobile phone case, and can also improve the strength and hardness of the back cover of the zirconia ceramic mobile phone case.
[0070] Comparing Example 1 with Examples 7-12, defective products were found in Examples 7-12, indicating that the yield rate of the back cover of the zirconia ceramic mobile phone case can be improved by optimizing the particle size of the agglomerated diamond powder, the pressure of the honeycomb resin pad grinding wheel, the type of grinding wheel, the particle size of silica, the pressure of the non-woven polishing wheel, and the type of polishing wheel in the grinding step.
[0071] Comparing Example 1 with Example 13-14, defective products appeared in Example 13-14, and the strength and hardness of Example 13-14 were not as good as those of Example 1, indicating that optimizing the sintering temperature, time and steps is beneficial to improving the yield rate of the back cover of the zirconia ceramic mobile phone case, and can also improve the strength and hardness of the back cover of the zirconia ceramic mobile phone case.
[0072] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A processing technology for a zirconia ceramic mobile phone back cover, characterized in that: The method comprises the following preparation steps: S1, dissolving polylactic acid and hydroxysilane coupling agent in an organic solvent, adding zirconium oxide powder, heating to 40-50°C, ultrasonicating, filtering, and drying to obtain pretreated zirconium oxide powder; S2, kneading the pretreated zirconium oxide powder, zinc oxide, nanocellulose crystals, the first dispersant, the binder and the plasticizer to obtain a mixture; S3, dry pressing the mixture with a dry press, cooling it, and placing it in a static press for isostatic pressing to obtain an embryo; S4, debinding and sintering the embryo body to obtain a ceramic body; S5. Use CNC machine tools to perform precision machining on the ceramic body to achieve the required size and shape accuracy; S6, using a grinder and a polisher in sequence to finely process the surface of the ceramic body; S7, performing beautification treatment and anti-fingerprint treatment on the surface treated ceramic body to obtain a ceramic mobile phone case back cover.
2. The processing technology of a zirconia ceramic mobile phone back cover according to claim 1, characterized in that: The weight percentages of the raw materials used in step S2 are as follows: Pre-treated zirconium oxide powder 50-60% Zinc oxide 8-15% Plasticizer 1-2% First dispersant 2-5% Binder 6-9% The rest is nanocellulose crystals.
3. The processing technology of a zirconia ceramic mobile phone back cover according to claim 2 is characterized in that: In step S1, the weight ratio of polylactic acid, hydroxysilane coupling agent, organic solvent and zirconium oxide powder is 1:0.5:5:(2-3).
4. The processing technology of a zirconia ceramic mobile phone back cover according to claim 1, characterized in that: The mixing temperature of step S2 is 170-180° C. and the mixing time is 1-2 h.
5. The processing technology of a zirconia ceramic mobile phone back cover according to claim 4 is characterized in that: In step S6, the ceramic body is ground, and the grinding process is as follows: 1) mixing agglomerated diamond micropowder, a second dispersant, a first suspending agent, a first lubricant and a first solvent to obtain a grinding liquid; 2) Use grinding fluid and honeycomb resin pad grinding wheel to grind the ceramic body. The pressure of the honeycomb resin pad grinding wheel is 90-100g / cm 2 , speed 60-90r / min, flow rate 500-600ml / min.
6. The processing technology of a zirconia ceramic mobile phone back cover according to claim 4, characterized in that: The weight ratio of the agglomerated diamond powder, the second dispersant, the first suspending agent, the first lubricant and the first solvent is 1:0.5:0.3:0.5:(4-6).
7. The processing technology of a zirconia ceramic mobile phone back cover according to claim 1, characterized in that: In step S6, the ceramic body is polished, and the polishing process is as follows: A: mixing silicon dioxide, sodium oxide, a third dispersant, a second suspending agent, a second lubricant and a second solvent to obtain a polishing liquid; B: Use polishing liquid and non-woven polishing wheel to polish the ceramic body. The pressure of the non-woven polishing wheel is 150-170g / cm 2 , speed 120-150r / min, flow rate 600-800ml / min.
8. The processing technology of a zirconia ceramic mobile phone back cover according to claim 1, characterized in that: The weight ratio of silicon dioxide, sodium oxide, the third dispersant, the second suspending agent, the second lubricant and the second solvent is 2:0.5:0.5:0.3:0.5:(4-6).
9. The processing technology of a zirconia ceramic mobile phone back cover according to claim 1, characterized in that: The pressure during the isostatic pressing is 220-280 MPa, and the holding time is 4-6 min.
10. The processing technology of a zirconia ceramic mobile phone back cover according to claim 1, characterized in that: The particle size of the agglomerated diamond powder is 50-100 nm, and the particle size of the silicon dioxide is 10-30 nm.
Citation Information
Patent Citations
Zirconia ceramic mobile phone rear cover and preparation method thereof
CN106187170A
Adhesive for zirconium oxide injection molding, feed and method of preparing zirconium oxide product
CN107473750A
Ceramic mobile-phone rear cover and preparation method thereof
CN107673757A
Processing method of zirconia ceramic mobile phone backboard
CN111410532A
3D printed zirconium oxide-based false tooth material and preparation method thereof
CN111704457A
Cited By
Preparation process of glue-free multilayer gradient zirconia porcelain block
CN121270238A